Restorative Policy Development in Health Dispute Resolution: A Comparative Study - Widjaja, Gunawan (Lafadz Jaya Publisher, 2025)
Dispute resolution in the health sector often involves complex and emotional processes. This study examines the development of restorative policies as an alternative to health dispute resolution using a comparative approach. Restorative policies, which focus on dialogue, mediation and consensus-based resolution, enable peaceful dispute resolution and maintain good relations between patients, health workers and healthcare institutions. This study revealed that the implementation of restorative policies can reduce emotional tension, accelerate resolution, and minimise stigma. Strong policy support, including training of professional mediators and strengthening health sector regulations, is required for the successful implementation of restorative methods. The main recommendation is the integration of restorative policies into a more humane and inclusive health dispute resolution system, providing satisfactory outcomes for all parties involved.